1983
DOI: 10.1207/s15327752jpa4701_5
|View full text |Cite
|
Sign up to set email alerts
|

An MMPI Subscale (Gd): To Identify Males with Gender Identity Conflicts

Abstract: This study reported on the development and cross-validation of a 31-item MMPI Gender Dysphoria subscale (Gd) which accurately discriminates between gender identity patients and matched controls, and identifies males with gender dysphoria syndrome. Both the validity and reliability of the Gd scale has been demonstrated and there is every expectation that the scale has excellent potential for clinical usage. In the construction of the Gd scale, we have addressed the major methodological problems of previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…(1) A scale for the differentiation of patients types in terms of fetishism and gender dysphoria had to be developed for this analysis because (a) while a validated fetishism scale does exist (Blanchard, 1989), it was not administered to a sufficient number of participants in the current study, and (b) the Gender Dysphoria subscale of the MMPI (Althof, Lothstein, Jones, & Shen, 1983) has been demonstrated to be inefficient (Langevin, Majpruz & Handy, 1990). …”
Section: Summary and Discussionmentioning
confidence: 99%
“…(1) A scale for the differentiation of patients types in terms of fetishism and gender dysphoria had to be developed for this analysis because (a) while a validated fetishism scale does exist (Blanchard, 1989), it was not administered to a sufficient number of participants in the current study, and (b) the Gender Dysphoria subscale of the MMPI (Althof, Lothstein, Jones, & Shen, 1983) has been demonstrated to be inefficient (Langevin, Majpruz & Handy, 1990). …”
Section: Summary and Discussionmentioning
confidence: 99%
“…Gender-identity confusion was measured using the Althof and Lothstein's (1983) scale which identifies males with gender-identity conflicts, e.g., I like adventure stories more than romantic stories, I often wished I were a girl. Bem's (1974) inventory was used to measure gender-role perceptions (i.e.…”
Section: Understanding the Metrosexual And Spornosexualmentioning
confidence: 99%
“…Furthermore, standardized psychiatric instruments and statistical analyses have rarely been applied to samples of TS patients. Many reports are casuistic or have serious methodological¯aws, such as selection bias and the lack of control groups, although notable exceptions exist (11). A recent Swedish study found that the ego-strength of TS patients was equal to normal controls', while patients with other gender identity disorders showed a signi®cantly weaker ego-strength than the controls (12).…”
Section: Introductionmentioning
confidence: 99%